Visualization Method in Mathematics Classes - Laxmi Rathour; Dragan Obradovic; Shiv Tiwari; Lakshmi Mishra; Vishnu Mishra (Computational Algorithms and Numerical Dimensions)
Developing students’ educational abilities has always been one of the most urgent. The more fully a student's potential is realized, the more success a person will be able to achieve in life and career. One of the effective technologies for activating learning is the method of visualizing educational information. The history of visualization in mathematics education is very long. Since the beginning of the year 1980s, mathematics professors have been interested in the practical challenges of teaching visualization, in the visualization of mathematics as an exhibit in school or in accordance with educational psychology, and are looking for theoretical frameworks.